Book Development of Volleyball Smash Exercises Variations for Volleyball Coaches in Palembang - Leo Sukma; Bangkit Seandi Taroreh (UNIB Press, 2022)
A variety of volleyball smash practice books has been successfully developed for volleyball club coaches in the city of Palembang. The development of a volleyball smash variation practice book for coaches was carried out using the ADDIE model development research method. Data collection techniques using questionnaires while data analysis using quantitative descriptive analysis. The validity of developing a volleyball smash variation practice book for coaches was assessed by five experts consisting of one volleyball learning expert and one language expert, as well as three volleyball coaches. The sample consisted of 20 volleyball club coaches in the city of Palembang who were selected by purposive sampling. The results of the study include: 1) A book on variations of volleyball smash training has been produced for coaches of volleyball clubs in Palembang with the validation results of linguists 91.33% (very worth using), ease of use of the book 93% (very worth using), material suitability 94.67% (very worth using), 2) The implementation results show 93% (very worth using).